2016
DOI: 10.3390/soc6030020
|View full text |Cite
|
Sign up to set email alerts
|

First Application of Robot Teaching in an Existing Industry 4.0 Environment: Does It Really Work?

Abstract: This article reports three case studies on the usability and acceptance of an industrial robotic prototype in the context of human-robot cooperation. The three case studies were conducted in the framework of a two-year project named AssistMe, which aims at developing different means of interaction for programming and using collaborative robots in a user-centered manner. Together with two industrial partners and a technological partner, two different application scenarios were implemented and studied with an of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…Technology acceptance was detected through four items taken from the Subjective Acceptance Questionnaire [48]; an example item is "The use of technology and automation systems increases my professional effectiveness" (Likert scale from 1 = totally disagree to 5 = totally agree). Cronbach's alpha was 0.75 for the white-collar sample and 0.77 for the blue-collar sample.…”
Section: Methodsmentioning
confidence: 99%
“…Technology acceptance was detected through four items taken from the Subjective Acceptance Questionnaire [48]; an example item is "The use of technology and automation systems increases my professional effectiveness" (Likert scale from 1 = totally disagree to 5 = totally agree). Cronbach's alpha was 0.75 for the white-collar sample and 0.77 for the blue-collar sample.…”
Section: Methodsmentioning
confidence: 99%
“…The Fourth Industrial Revolution is not limited to industrial production. It is manifested in all aspects of the society, including technology (Xu et al, 2013;Lalanda et al, 2017;Theorin et al, 2017), production (Kube and Rinn, 2014;Webster, 2015), consumption and business (Sommer, 2015;Gentner, 2016;Ivanov et al, 2016), and it is influencing every field of human life (Home et al, 2015;Singer, 2015;Qin and Cheng, 2016;Sackey and Bester, 2016;Weiss et al, 2016). So far, we have not reached a concrete understanding about this technological trend.…”
Section: Introductionmentioning
confidence: 99%
“…However, only qualified and highly educated employee will be able to control such technologies, so collaboration between the industry and university should be more intense [23]. For example, a study on the usability and acceptance of an industrial prototype in relation to collaborative robots with humans in [24] has suggested the urgency of adaptation of assistive robot systems. It is well known that the collaborative robots (cobots) are very expensive and they are not easily accessible by common students and researchers, except for those who work in leading research institution or industry.…”
Section: Introductionmentioning
confidence: 99%